Improving the caring character of the school environment through providing group guidance services using discussion techniques - Lubis, Muhammad Alridho; Dina, Risma; Putra, San (Universitas Islam Negeri Raden Intan Lampung, 2023)
The low character of caring for the school environment in students makes the school environment dirty and causes damage to school facilities, even though this character is crucial in forming a caring and responsible attitude in students. This research aims to improve the caring character of the school environment in students through group guidance services using discussion techniques. The research method used is action research with a one group pre-test and post-test design. The research was carried out in 2 cycles, each cycle consisting of planning, implementation, evaluation and reflection. The research sample used purposive sampling consisting of 10 students who had a low level of concern for the school environment. Data collection was carried out by distributing a character scale that cared about the school environment after taking action. The results of the research show that discussion technique group guidance services can improve the caring character of the school environment in students.